S4D AS A CHARACTER IN THE DEVELOPMENT OF THE INDONESIAN PHYSICAL EDUCATION AND SPORTS PROFESSION IN THE 4.0 INDUSTRIAL REVOLUTION ERA - Ana Lestarina Sembiring (Indonesia Sport Journal, 2021)
The purpose of this article is to discuss the development of the physical and sports professions in Indonesia in advancing the character of the industrial revolution 4.0 program towards the 2030 sustainable development program, achievements in the era of sustainable development goals (SDGs). In the development of the 4.0 revolution program, not only skills and technology are needed but the skills of a product in critical thinking, creative, innovative, learning technology, trying new and rich things, and being able to collaborate to realize new sciences. Through this S4D, it is hoped that it can maximize sports goals in accordance with RI Law NO. 3 of 2005, so that it can support the http://sdgs.bappenas.go.id/target-4 program in sustainable development efforts and achieving the era of sustainable Development Goals 2030. Keywords: S4D, UU RI NO 3 THAUN 2005